2009
DOI: 10.1158/0008-5472.sabcs-1026
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node detection in breast cancer patients by real-time virtual sonography constructed with three-dimensional computed tomography-lymphography.

Abstract: #1026 Background: Ultrasonography (US) is one tool for preoperative diagnosis of lymph node metastases in breast cancer. However, US cannot detect true sentinel lymph nodes (SLNs).
 Methods: We identified SLNs in 60 clinically node-negative breast cancer patients using a real-time virtual sonography (RVS) system to display in real time a virtual multi-planar reconstruction obtained from computed tomography (CT) volume data corresponding to the same cross-sectional image from US. CT vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Nakano et al [10] first reported that RVS systems can identify enhancing breast lesions visualized with MRI with excellent accuracy. We recently reported that RVS systems can identify SLNs by using data from CT lymphography [9]. In the present study, we used an RVS system and 3DCT-LG to preoperatively detect SLNs and evaluate SLN status by US.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nakano et al [10] first reported that RVS systems can identify enhancing breast lesions visualized with MRI with excellent accuracy. We recently reported that RVS systems can identify SLNs by using data from CT lymphography [9]. In the present study, we used an RVS system and 3DCT-LG to preoperatively detect SLNs and evaluate SLN status by US.…”
Section: Discussionmentioning
confidence: 98%
“…A real-time virtual sonography (RVS) system [8] was recently developed that shows in real time the virtual multiplanar reconstruction (MPR) CT image corresponding to the image from ultrasonography (US). We have applied RVS conducted using 3DCT-LG to the preoperative detection of SLNs and prediction of SLN metastasis in breast cancer patients [9]. Preoperative ultrasonographic diagnosis of metastasis in axillary lymph nodes may prove useful.…”
Section: Introductionmentioning
confidence: 99%
“…Sentinel lymph nodes are likely involved in the spread of tumor cells and therefore the status of these nodes are seen as an independent additional factor in the prognosis in disease (1). Diagnostic techniques such as ultrasound, magnetic resonance imaging and histological confirmation (biopsy) are used to investigate a possible metastasis to the sentinel lymph nodes (2)(3)(4). In the case of head and neck cancer, where a metastasis is confirmed, the removal of the sentinel lymph node is the primary option to increase the survival rate of the patient (5).…”
Section: Publications Digest Ultrasound and Nano/microbubbles For Molmentioning
confidence: 99%
“…As an example, the work of Karakatas et al (20) was used, who showed in their publication a mitochondrion covered with 565 gold nanoparticles (13 nm diameter). From the calculations it was concluded that the dose enhancement ratios [1] were the highest in the kilovolt range, [2] depend on the dimensions of the mitochondrion, [3] the number of gold nanoparticles, and [4] the thickness of the gold nanoparticle coating. The presented work suggests further investigation of the role of the mitochondrium in cellular response to radiation and a novel possibility for radiation therapy where the mitochondria are the target.…”
Section: Targeting Mitochondria In Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation